2012
DOI: 10.1007/s11051-012-1300-z
|View full text |Cite
|
Sign up to set email alerts
|

Validity range of centrifuges for the regulation of nanomaterials: from classification to as-tested coronas

Abstract: Granulometry is the regulatory category where the differences between traditional materials and nanomaterials culminate. Reported herein is a careful validation of methods for the quantification of dispersability and size distribution in relevant media, and for the classification according to the EC nanodefinition recommendation. Suspension-based techniques can assess the nanodefinition only if the material in question is reasonably well dispersed. Using dispersed material of several chemical compositions (org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 60 publications
0
46
1
1
Order By: Relevance
“…6 (Wohlleben, 2012;Wohlleben et al, 2011Wohlleben et al, , 2013Walter et al, 2014). The size distribution analyses of pristine n-CuPc and Frag n-CuPc in RPMI showed that the dispersion of pristine n-CuPc contained smaller particles than the Frag n-CuPc.…”
Section: Characterization Of Pristine N-cupc and Sanding Fragments Inmentioning
confidence: 98%
“…6 (Wohlleben, 2012;Wohlleben et al, 2011Wohlleben et al, , 2013Walter et al, 2014). The size distribution analyses of pristine n-CuPc and Frag n-CuPc in RPMI showed that the dispersion of pristine n-CuPc contained smaller particles than the Frag n-CuPc.…”
Section: Characterization Of Pristine N-cupc and Sanding Fragments Inmentioning
confidence: 98%
“…Characterization of the NMs as prepared test items was performed using analytical ultracentrifugation (AUC) as described by Wohlleben (2012). Test substance stock dispersions were prepared 24 h before application onto the PCLuS and were analyzed on the day of exposure using the Beckman Ultracentrifuge XLI™ with integrated interference optics (Beckman Coulter, Palo Alto, CA, USA).…”
Section: Characterization Of the Nanoparticles As Prepared Test Itemsmentioning
confidence: 99%
“…Centrifuges are applied in various disciplines mainly in material and particle technology like for separation (Sahuquillo et al, 1999;Kuang et al, 2015), for nanomaterials classification (Wohlleben, 2012), casting (Huisman et al, 1994;Liu and Barnett, 2002;Dikel et al, 2005;Velhinho and Rocha, 2011), combustion (Merzhanov, 1995), but also in areas like geology (Gopal Madabhushi, 2004;Costa et al, 2016), life sciences in plants (Musgrave et al, 2009;Herranz et al, 2013;Hoson and Wakabayashi, 2015), single cells (Loesberg et al, 2006;Tavakolinejad et al, 2015), animals (van Loon, 2001;van Loon et al, 2005;Tateishi et al, 2015) and humans (Akima et al, 2005;van Loon et al, 2012;Goswami et al, 2015).…”
Section: Introductionmentioning
confidence: 99%